Step by step tools to identify ecological intensification alternatives for banana cropping systems (2018)
Ecological intensification (EI) is an approach to improve cropping system performance by synchronizing ecological and production processes to increase the returns from external inputs, labor, nutrients, water and sunlight; reduce losses to abiotic and biotic stress and reduce the negative off-field impacts. The framework has been shown applicable to both high-input and low-input systems, but a stepwise integrated systems approach has yet to be proposed to guide the diagnosis of intensification potential. We analyze work done on diverse banana cropping systems grown under different biotic and abiotic constraints, to propose six sequential themes for diagnosing intensification potential. First, is the current cropping system threatened by a major biotic threat like Fusarium wilt or banana bunchy top disease? Recovering banana production in the presence of these constraints requires system redesign from perennial production to planned and monitored recovery cycles based on pathogen/pest levels, especially in the absence of resistant cultivars. Second, what is the cropping system yield gap in terms of available light, water and temperature, both averages and extreme events? Does the banana density optimize bunch production for the specific cropping system? Do the other crops generate yield in accordance with their status in the system? Third, what is the input-output for macro- and micro-nutrients and what internal recycling operates? Fourth, is the soil protected from degradation and managed to ensure an improving structure, aeration and drainage for roots and soil biota? Fifth, can losses from pests and pathogens, and environmental costs of their management be reduced through substitute practices and system redesign to disfavor pests and pathogens and favor natural control? Sixth, are there other yield gap factors? Twenty questions addressing these six themes were synthesized to twelve steps to rate high, medium or low ecological intensification potential. The seven systems studied showed highly variable potential for EI. Systems varied in individual crop yield gap issues, but also system yield gaps with relevance to improved sustainability and resilience. The selection of multi-functional practices for further testing strengthens the orientation towards system integration as a pathway to increased productivity and efficiency. Gaps in the available tools to complete this process were identified and discussed